PENYULUHAN HUKUM BENTUKAN KOPERASI TAMBANG UNTUK PERTAMBANGAN RAKYAT DI KABUPATEN SUKABUMI - Agatha Lafentia; Michelle Prawira; Rayhan Fiqi Fansuri; Gunardi Gunardi; Ahmad Redi; Lewiandy Lewiandy (Jurnal Hukum Adigama, 2021)
People’s mining is a form of people's participation in mining business activities in areas that contain mining materials. As written in Article 33 paragraph 3 of the 1945 Constitution, the earth, water and natural resources contained therein are intended for the prosperity of the Indonesian people. As an actual form of implementation of Article 33 paragraph 3 of the 1945 Constitution, the people should actually be given a share in the world of mining. However, all people's mining activities are often hindered by the messy licensing procedure or what is commonly known by the acronym IPR (People's Mining Permit). In general, people or groups entitled to IPR are local residents, be they individuals or community groups and cooperatives, this is in accordance with what is mandated in Article 67 paragraph (1) of Law no. 4 of 2009 concerning Mineral and Coal Mining. Cooperatives in their activities are based on the principles of the people's economic movement which are based on the principle of kinship. This study aims to determine how mining cooperatives are formed in the eyes of Indonesian law and to clarify the basis for their formation. The results showed that the establishment of a cooperative to assist community miners in managing the mining process was normative, safe, and smooth